Occurrence of arbuscular mycorrhizal fungi on King George Island, South Shetland Islands, Antarctica - BARBOSA,MARISÂNGELA V. (2017)
ABSTRACT Arbuscular mycorrhizal fungi make up an important ecological niche in ecosystems, and knowledge of their diversity in extreme environments is still incipient. The objective of this work was to evaluate the density and diversity of arbuscular mycorrhizal fungi in the soil of King George Island in the South Shetland Islands archipelago, Antarctica. For that, soil and roots of Deschampsia antarctica were collected at the brazilian research station in Antarctica. The spore density, species diversity and mycorrhizal colonization in the roots were evaluated. There was a low density of spores (27.4 ± 17.7) and root mycorrhizal colonization (6 ± 5.1%), which did not present statistical difference. Four species of arbuscular mycorrhizal fungi were identified, distributed in two genera: three species of the genus Glomus (Glomus sp1, Glomus sp2 and Glomus sp3) and one of the genus Acaulospora, which was identified at species level (Acaulospora mellea). Greater soil diversity was verified with pH 5.9 and phosphorus concentration of 111 mg dm-3, occurring two species of genus Glomus and A. mellea. Based on literature data, this may be the first record of this species of Acaulospora mellea in Antarctic soils, colonizing D. antarctica plants.